Help (not) wanted immigration politics in Japan - Strausz, Michael (Albany State University of New York Press, 2019)
"In Help (Not) Wanted, Michael Strausz offers an original and provocative answer to a question that has long perplexed observers of Japan: Why has Japan's immigration policy remained so restrictive, especially in light of economic, demographic, and international political forces that are pushing Japan to admit more immigrants? Drawing upon insights that he developed during twenty-two months of intensive field research in Japan, Strausz ultimately argues that Japan's immigration policy has remained restrictive for two reasons: first, Japan's labor-intensive businesses have failed to defeat anti-immigration forces within the Japanese state, particularly those in the Ministry of Justice and the Japanese Diet; and second, no influential strain of elite thought in postwar Japan exists to support the idea that significant numbers of foreign nationals have a legitimate claim to residency and membership. This book is particularly timely at a moment shaped by Brexit, the election of Trump, and the rise of anti-immigrant political parties and nativist rhetoric across the globe"--
Foreign Laborers, Not Immigrants -- Help Wanted: Immigration Restriction in a World of Labor Shortages, Aging Populations, and Refugee Crises -- Minority Rights and Minority Invisibility: Oldcomer Koreans in Japan -- The Crow is White: Foreign Labor and the Japanese State -- Asylum as Exception -- Is Another Japan Possible? Public Opinion and Immigration Reformists -- Japanese Immigration in the Age of Trump.
Includes bibliographical references and index.
Keywords: Foreign workers -- Japan; Japan -- Emigration and immigration -- Government policy; Japan -- Emigration and immigration -- Social aspects